EVALUASI DAMPAK SOSIAL EKONOMI RELOKASI PEDAGANG KAKI LIMA MENJADI PUJASERA DI KOTA SEMARANG TAHUN 2013 - Whinarko .; Rr Hermini S; Sulistyowati . (Journal of Politic and Government Studies, 2014)
The aim of this research is to know how much is the socio-economic impacts relocation of street vendors at the intersection of Simpang Lima and Pahlawan streets of Semarang City. This research used inferensial analysis and deskriptif percentase. To know the socio-economic impacts, it was done by interviewing and questionairring some street vendors at the intersection of Simpang Lima and Pahlawan streets of Semarang City. The result of this research showed that the social impact of the relocation of street vendors at the intersection of Simpang Lima and a Pahlawan streets of Semarang City a positive impact in terms of the social economy that is improve social relationships among traders, feasibility and convenience of business and can increase the income of street vendors. Still a constraint in terms of infrastructure and facilities